Implikasi Poligami dalam Interpretasi Al-Qur'an: Pandangan Ulama, Tafsir Kontemporer, dan Perspektif Kementerian Agama RI - S, Riyandi (Yayasan Madinah Al-Aziziyah, 2023)
Polygamy is a term that refers to the practice of marriage in which a man has more than one wife simultaneously within the bounds of legality. This practice can be found in various cultures and religions worldwide, but it is most common in the contexts of religions that permit or regulate polygamy. In Islam, for example, polygamy is allowed with certain requirements that must be fulfilled by a man who wishes to have more than one wife. Other cultures and societies also have forms of polygamy that are recognized legally or socially. This study aims to discuss the implications of polygamy in the interpretation of the Qur'an: the views of scholars, contemporary interpretations, and the perspective of the Ministry of Religious Affairs of the Republic of Indonesia. The research methodology employed in this study is literature review. The findings of this study reveal that in the field of Qur'anic exegesis (tafsir) and Islamic jurisprudence (fiqh) related to marriage, there are approaches that permit the practice of polygamy under three specific conditions. Firstly, a wife's medical condition that prevents her from bearing children is considered as one of the important criteria. Secondly, when a wife enters menopause and can no longer fulfill the needs of her husband who is still in a physically strong condition, and to avoid the risk of committing adultery. Thirdly, permission for polygamy can be granted when the number of women significantly exceeds the number of men. However, the requirement of treating wives fairly must always apply.